The diagnostic value of the olfactory evaluation for congenital hypogonadotropic hypogonadism - Yu, Bingqing; Chen, Kepu; Mao, Jiangfeng; Hou, Bo; You, Hui; Wang, Xi; Nie, Min; Huang, Qibin; Zhang, Rui; Zhu, Yiyi; Sun, Bang; Feng, Feng; et al. (Frontiers in Endocrinology, 2022)
Objective The aim of this study was to evaluate the diagnostic accuracy of different olfactory evaluation tools in congenital hypogonadotropic hypogonadism (CHH) patients. Methods Seventy-one CHH patients were prospectively recruited at Peking Union Medical College Hospital between November 2020 and July 2021. The Chinese Olfactory Function Test (COFT) and Self-reported Olfactory Scale (SROS) were adapted as the subjective tools for the evaluation of olfactory function, and magnetic resonance imaging of olfactory apparatus (MRI-OA) was the objective tool. The olfactory bulb volume (OBV) and the olfactory sulcus depth (OSD) were quantified. Results Based on the COFT, 36 patients were categorized as having normosmic CHH (nCHH), and the other 35 patients were categorized as having Kallmann syndrome (KS). Among nCHH patients, 35 patients were classified as having normal olfaction and 1 patient had abnormal olfaction by SROS. For KS patients, there were 30 patients grouped into abnormal olfaction, while 5 patients had normal olfaction by SROS. For MRI-OA, 67% (18/27) of nCHH patients showed normal olfactory apparatus, and 33% (9/27) showed bilateral or unilateral olfactory bulb aplasia or hypoplasia. Among KS patients, 96% (27/28) of patients showed bilateral olfactory bulb hypoplasia or aplasia, and 4% (1/28) of patients showed normal olfactory apparatus. All six patients with unilateral olfactory bulb aplasia and three patients with bilateral olfactory bulb aplasia showed normal olfactory function. The accuracy of the SROS in the diagnosis of nCHH and KS was 91.5%, with a sensitivity of 0.857 and a specificity of 0.972, while the accuracy of MRI-OA is 92.7%, with a sensitivity of 0.964 and a specificity of 0.889. Conclusion SROS and MRI-OA both showed high accuracy to distinguish between KS and nCHH. The abnormal structure of the olfactory apparatus was relatively common in nCHH patients. CHH patients with unilateral olfactory bulb aplasia dysplasia usually had normal olfaction. Normal olfaction without apparent olfactory bulbs is rare but occurred in male CHH patients.